Reproduksi pengetahuan atas eksotisme tubuh perempuan: identitas oriental dalam grup facebook ‘indonesia tempo dulu’ - Suwito, Kandi Aryani (Jurnal Studi Komunikasi, 2019)
This article aims to explore the reproduction of knowledge on the exotics of the body materialised through photographs in the Facebook group ‘Indonesia Tempo Dulu’ which is a memory site for the construction of oriental identities framed in the complexity of past history and the present context. This problem is a study that uses visual methodology as a method in finding answers to how digital culture that enables the transmission of old media, in this case photographs, becomes the domain for identity reproduction. History is not only presented as a form of romanticism which is a casual factor for the emergence of digital technology as a product of modernity but as a construction that opens up spaces of possible heterogeneity in defining and performing identities, especially in social media. This study uses postcolonial theories in exploring important concepts such as ‘memory’, ‘domination’, ‘subjugation’ and ‘power’